Secondary dengue infection in schoolchildren in a dengue endemic area in the State of Rio de Janeiro, Brazil - Cunha, Rivaldo Venâncio da; Dias, Márcio; Nogueira, Rita M. R.; Chagas, Nelson; Miagostovich, Marize P.; Schtzmayr, Hermann G. (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
A seroepidemiologic survey was carried out in schoolchildren from public schools of the Niterói municipality, state of Rio de Janeiro, Brazil, after a period of sequential epidemics by dengue virus type 1 and 2 (DEN-1 and DEN-2). 450 blood samples were obtained by fingertip puncture and collected on filter paper discs. The hemagglutination inhibition (HAI) test was carried out using DEN-1 and DEN-2 antigens. HAI titres were demonstrated in 66% (297/450) of the sera and the geometric means of the titres were 1/182 and 1/71 for DEN-1 and DEN-2, respectively. Secondary infections were observed in 61% (181/297) of positive cases. Among these, 75% (135/181) were under fifteen years old. No dengue haemorrhagic fever (DHF) was reported in these children. Asymptomatic or oligosymptomatic infections were detected in 56% of the studied population. The absolute and relative frequencies of positive tests by age group and sex did not evidence statistically significant difference. The number of individuals infected probably produced a immunologic barrier responsible for the non occurrence of dengue epidemic in the latter years.